Catalysis: Spatially Confined Hybridization of Nanometer‐Sized NiFe Hydroxides into Nitrogen‐Doped Graphene Frameworks Leading to Superior Oxygen Evolution Reactivity (Adv. Mater. 30/2015). (August 2015) - Tang, Cheng; Wang, Han‐Sen; Wang, Hao‐Fan; Zhang, Qiang; Tian, Gui‐Li; Nie, Jing‐Qi; Wei, Fei
<x xml:space="preserve">Abstract</x> A hydroxide/graphene hybrid electrocatalyst for oxygen evolution reaction is proposed by Q. Zhang and co‐workers, as described on page 4516. Nanosized hydroxide active centers are uniformly and strongly hybridized into a nitrogen‐doped graphene framework via defect‐anchored nucleation and spatially confined growth. The as‐obtained hydroxide/graphene is demonstrated to overperform commercial Ir/C catalysts and compete favorably against reported alternatives for high‐performance oxygen evolution reactivity.